SISTEM INFORMASI PEMBUATAN SURAT KETERANGAN TIDAK MAMPU BERBASIS WEB DI DESA PESANGGRAHAN - Yasin, Muhammad; Gunawan, Ahmad; Samad, Abdus (Jurnal Riset Sistem Informasi, 2025)
Village-level public service processes frequently encounter obstacles like drawn-out manual processes, restricted information availability, and rigid service schedules. In order to increase the effectiveness of village administrative services, specifically in the creation of the Certificate of Inability (SKTM), this project intends to develop a web-based information system. The waterfall technique, which comprises phases for requirements analysis, system design, implementation, testing, and maintenance, is used to construct the system. The PHP CodeIgniter framework and MySQL database are among the technologies utilized. According to test results, this technology can improve transparency and service efficacy, speed up document processing, and make it easier for residents to access services online. It is anticipated that this method will be a creative way to facilitate the digitization of village government.